Molecular Clocks and Archeogenomics of a Late Period Egyptian Date Palm Leaf Reveal Introgression from Wild Relatives and Add Timestamps on the Domestication. (30th June 2021) - Pérez-Escobar, Oscar A; Bellot, Sidonie; Przelomska, Natalia A S; Flowers, Jonathan M; Nesbitt, Mark; Ryan, Philippa; Gutaker, Rafal M; Gros-Balthazard, Muriel; Wells, Tom; Kuhnhäuser, Benedikt G; Schley, Rowan; Bogarín, Diego; et al.
Abstract: The date palm, Phoenix dactylifera, has been a cornerstone of Middle Eastern and North African agriculture for millennia. It was first domesticated in the Persian Gulf, and its evolution appears to have been influenced by gene flow from two wild relatives, P. theophrasti, currently restricted to Crete and Turkey, and P. sylvestris, widespread from Bangladesh to the West Himalayas. Genomes of ancient date palm seeds show that gene flow from P. theophrasti to P. dactylifera may have occurred by ∼2, 200 years ago, but traces of P. sylvestris could not be detected. We here integrate archeogenomics of a ∼2, 100-year-old P. dactylifera leaf from Saqqara (Egypt), molecular-clock dating, and coalescence approaches with population genomic tests, to probe the hybridization between the date palm and its two closest relatives and provide minimum and maximum timestamps for its reticulated evolution. The Saqqara date palm shares a close genetic affinity with North African date palm populations, and we find clear genomic admixture from both P. theophrasti, and P. sylvestris, indicating that both had contributed to the date palm genome by 2, 100 years ago. Molecular-clocks placed the divergence of P. theophrasti from P. dactylifera / P. sylvestris and that of P. dactylifera from P. sylvestris in the Upper Miocene, but strongly supported, conflicting topologies point to older gene flow between P. theophrasti and P. dactylifera, and P. sylvestris and P. dactylifera . Our work highlights the ancient hybrid origin of the date palms, and prompts the investigation of the functional significance of genetic material introgressed from both close relatives, which in turn could prove useful for modern date palm breeding.